Erasure : a novel - Everett, Percival (Graywolf Press, 2001)
Thelonius "Monk" Ellison is an erudite, accomplished but seldom-read author who insists on writing obscure literary papers rather than the so-called "ghetto prose" that would make him a commercial success. He finally succumbs to temptation after seeing the Oberlin-educated author of We's Lives in da Ghetto during her appearance on a talk show, firing back with a parody called My Pafology, which he submits to his startled agent under the gangsta pseudonym of Stagg R. Leigh. Ellison quickly finds himself with a six-figure advance from a major house, a multimillion-dollar offer for the movie rights and a monster bestseller on his hands. The money helps with a family crisis, allowing Ellison to care for his widowed mother as she drifts into the fog of Alzheimer's, but it doesn't ease the pain after his sister, a physician, is shot by right-wing fanatics for performing abortions. The dark side of wealth surfaces when both the movie mogul and talk-show host demand to meet the nonexistent Leigh, forcing Ellison to don a disguise and invent a sullen, enigmatic character to meet the demands of the market. The final indignity occurs when Ellison becomes a judge for a major book award and My Pafology (title changed to Fuck) gets nominated, forcing the author to come to terms with his perverse literary joke. Percival's talent is multifaceted, sparked by a satiric brilliance that could place him alongside Wright and Ellison as he skewers the conventions of racial and political correctness. (Sept. 21)Forecast: Everett has been well-reviewed before, but his latest far surpasses his previous efforts. Passionate word of mouth (of which there should be plenty), rave reviews (ditto) and the startling cover (a young, smiling black boy holding a toy gun to his head) could help turn this into a genuine publishing event.